Fish Red Blood Cells Modulate Immune Genes in Response to Bacterial Inclusion Bodies Made of TNFα and a G-VHSV Fragment - Puente-Marin, Sara; Thwaite, Rosemary; Mercado, Luis; Coll, Julio; Roher, Nerea; Ortega-Villaizan, Maria Del Mar (Frontiers in Immunology, 2019)
Fish Red-Blood Cells (RBCs) are nucleated cells that can modulate the expression of different sets of genes in response to stimuli, playing an active role in the homeostasis of the fish immune system. Nowadays, vaccination is one of the main ways to control and prevent viral diseases in aquaculture and the development of novel vaccination approaches is a focal point in fish vaccinology. One of the strategies that has recently emerged is the use of nanostructured recombinant proteins. Nanostructured cytokines have already been shown to immunostimulate and protect fish against bacterial infections. To explore the role of RBCs in the immune response to two nanostructured recombinant proteins, TNFα and a G-VHSV protein fragment, we performed different in vitro and in vivo studies. We show for the first time that trout RBCs are able to endocytose nanostructured TNFα and G-VHSV protein fragment in vitro, despite not being phagocytic cells and in response to nanostructured TNFα and G-VHSV fragment, the expression of different immune genes could be modulated.